2016
DOI: 10.1177/0963721416651960
|View full text |Cite
|
Sign up to set email alerts
|

A More Complete Picture of Personality

Abstract: Personality profiles describe individual persons’ locations on multiple trait dimensions and enable calculation of profile similarity indices for individual persons and dyads. They are easily misinterpreted, however, unless two components are distinguished: a normative component comprising the sample means of the variables and a distinctive component reflecting the given individual’s deviations from those means. These two profile components provide different kinds of information. Focusing on person-perception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Thus, in the current studies, a good judge was defined as someone who can determine a target's unique self-reported profile of traits, such as whether he or she is more talkative than creative and more kind than anxious, relative to other people. Such a profile approach to assessing accuracy provides a holistic index of whether the perceiver understands the target by examining the extent to which he or she has developed a valid impression of the target's overall patterning traits (see Borkenau & Leising, 2016, for a review). Further, this indicator of accuracy controls for the normativity of impressions (Biesanz, 2010;Cronbach, 1955;Furr, 2008), the extent to which a perceiver views targets as similar to the average personality profile.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the current studies, a good judge was defined as someone who can determine a target's unique self-reported profile of traits, such as whether he or she is more talkative than creative and more kind than anxious, relative to other people. Such a profile approach to assessing accuracy provides a holistic index of whether the perceiver understands the target by examining the extent to which he or she has developed a valid impression of the target's overall patterning traits (see Borkenau & Leising, 2016, for a review). Further, this indicator of accuracy controls for the normativity of impressions (Biesanz, 2010;Cronbach, 1955;Furr, 2008), the extent to which a perceiver views targets as similar to the average personality profile.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of profile agreement is based on the profile that each individual has in self-and other-ratings across a number of traits (Borkenau & Leising, 2016;Furr, 2008). For example, a person may rate him-or herself as high on helpfulness, intermediate on achievement orientation, and low on talkativeness; if an external rater provides the same relative ratings of the target on these traits, agreement will be high.…”
Section: Profile Agreementmentioning
confidence: 99%
“…Apart from the insight into the contribution of normativeness to agreement, an important benefit of profile agreement analysis is that it provides agreement estimates at the level of the individual, which can be linked with various individual-level correlates. Although profile analysis has a long history, it has only recently seen widespread use in personality research (Borkenau & Leising, 2016). Crosscultural research on profile agreement is scant.…”
Section: Profile Agreementmentioning
confidence: 99%
See 2 more Smart Citations